A head‐to‐head comparison of ixekizumab vs. guselkumab in patients with moderate‐to‐severe plaque psoriasis: 24‐week efficacy and safety results from a randomized, double‐blinded trial. (1st June 2021) - Blauvelt, A.; Leonardi, C.; Elewski, B.; Crowley, J.J.; Guenther, L.C.; Gooderham, M.; Langley, R.G.; Vender, R.; Pinter, A.; Griffiths, C.E.M.; Tada, Y.; Elmaraghy, H.; et al.
Summary: Background: Significantly more patients with moderate‐to‐severe plaque psoriasis treated with the interleukin (IL)‐17A inhibitor ixekizumab vs. the IL‐23p19 inhibitor guselkumab in the IXORA‐R head‐to‐head trial achieved 100% improvement in Psoriasis Area and Severity Index (PASI 100) at week 12. Objectives: To compare skin and nail clearance and patient‐reported outcomes for ixekizumab vs. guselkumab, up to week 24. Methods: IXORA‐R enrolled adults with moderate‐to‐severe plaque psoriasis, defined as static Physician's Global Assessment ≥ 3, PASI ≥ 12 and involved body surface area ≥ 10%. Statistical comparisons were performed using the Cochran–Mantel–Haenszel test stratified by pooled site. Time‐to‐first‐event comparisons were performed using Kaplan–Meier analysis, and P ‐values were generated using adjusted log‐rank tests stratified by treatment group. Cumulative days at clinical and patient‐reported responses were compared by ancova . The trial was registered with ClinicalTrials.gov (NCT03573323). Results: Of the 1027 patients randomly assigned, 90% completed the trial (465 of 520 ixekizumab and 459 of 507 guselkumab). As early as week 2 and through week 16, more patients on ixekizumab achieved PASI 100 ( P < 0·01). At week 24, ixekizumab was noninferior to guselkumab (50% vs. 52%, difference −2·3%), with no statistically significant difference in PASI 100 ( P = 0·41). More patients receiving ixekizumab showed completely clear nails at week 24 (52% vs. 31%, P = 0·007). The median time to first PASI 50/75/90 and PASI 100 were 2 and 7·5 weeks shorter, respectively, for patients on ixekizumab vs. guselkumab ( P < 0·001). Patients on ixekizumab also had a greater cumulative benefit, with more days at PASI 90 and 100, with Dermatology Life Quality Index of 0 or 1, and itch free ( P < 0·05). The frequency of serious adverse events was 3% for each group, with no new safety signals. Conclusions: Ixekizumab was noninferior to guselkumab in complete skin clearance and superior in clearing nails at week 24. Ixekizumab cleared skin more rapidly in patients with moderate‐to‐severe plaque psoriasis, with a greater cumulative benefit, than guselkumab. Overall, the safety findings were consistent with the known safety profile for ixekizumab.